Analisis Karakteristik Elektrik Onggok Singkong sebagai Pasta Bio-Baterai - Tri Sumanzaya; Amir Supriyanto; Gurum Ahmad Pauzi (Jurnal Teori dan Aplikasi Fisika, 2019)
Bio-battery is a battery with paste that is made of natural materials. Bio-battery produce electrical power by using electrolyte cassava pulp and Cu-Zn electrode. Design of bio-batteries are made by 20 cell of dry cell battery type R20S IEC/UM-1/D 1,5 volt and arranged in series. Cassava pulp variation are new cassava pulp and pulp with fermentation for 48 hours, 96 hours, and 144 hours. The measurement of the electrical characteristics using 7 watt LED DC for 12 hours. The maximum voltage when the load is released which genereted by new cassava pulp is 16,76 volt, fermented for 48 hours is 19,28 volt, fermented for 96 hours is 20,00 volt, and fermented for 144 hours is 20,30 volt. The variety of cassava pulp which has the best electrical characteristics is fermented cassava pulp for 144 hours. It could turn on the lamp with bright lights. The results showed that the longer the fermentation time of cassava pulp caused the electrical conductivity was increased.